Judicial Encounters with International Commercial Arbitration in the US and Australia - Antonia Ambrose (Washington University Global Studies Law Review, 2025)
Arbitration clauses are increasingly standard in contract formation, including in international business. In 1985, the United Nations Commission on International Trade Law promulgated its Model Law on International Commercial Arbitration. Since then, it has been adopted in various forms in 118 jurisdictions worldwide. In today’s globalized economy, the Model Law’s adoption and use in local judicial enforcement and interpretation of contracts between international parties presents an important consideration and choice of law issue. This note considers two examples of judicial interpretation of international commercial arbitration law, one case from Australia and another from the United States. First, this note lays out a brief history of international commercial arbitration and its legal development, focusing on the development and adoption of the Model Law. Then, it examines the legal opinions of Oracle Am., Inc. v. Myriad Grp. A.G. and Dialogue Consulting Pty Ltd v. Instagram, Inc and analyses how these opinions illustrate diverse views by courts as interpreters and enforcers of international commercial arbitration contracts. As a litmus test for the status of the Model Law’s incorporation, the cases suggest that Australia is a more receptive forum for arbitration enforcement litigation and depicts the flexible judicial perspective required to interact with the Model Law and other international standards of arbitration law.
Keywords: arbitration clause; contract formation; international business; trade law; international commercial arbitration; Oracle Am Inc v Myriad Grp AG; Dialogue Consulting Pty Ltd v. Instagram